Disordering the Establishment : Participatory Art and Institutional Critique in France, 1958-1981 - Woodruff, Lily, 1981- (Book collections on Project MUSE., 2020)
"DISORDERING THE ESTABLISHMENT tells the story of the generation of French artists who used new aesthetic forms to critique artistic and political institutions in the years leading up to and following May '68. Daniel Buren, Andre Cadere and other artists brought art to the streets, using it to question assumptions of what art should be, and where it should be seen. Focusing on four artists - or art groups - Lily Woodruff gives a nuanced account of how artists employed participatory and collective projects in varying but complementary attempts to question and redefine their historical moment. The book has four chapters. Chapter 1 describes the 1966 Groupe de Recherche d'Art Visuel (GRAV), a collective that created works asking viewers to perpetually negotiate with illusions constructed by artists, while resisting mystification. Social engineers within the context of the art world, GRAV constructed instability against the technocrats through street action that ambiguously reproduced the Establishment's techniques from a Marxian perspective. Chapter 2 highlights Daniel Buren's early gallery and street installations, which worked to decenter the viewer and critique French cultural policy through camouflage. By adopting the visual language of his environment, Buren's work played between visibility and invisibility, provocatively alienating viewers. In chapter 3, Woodruff explains how Andre Cadere's work developed on the theme of artistic autonomy in tension with avant-garde artistic strategies of the time. A migrant who relocated to Western Europe to escape persecution in communist Romania, Cadere produced a single type of iconic work based on systematically repeated formulas that were intended to neutralize his own subjectivity and the significance of the viewer's interpretation. Similar to Buren, his work was produced in both everyday and institutional spaces. Chapter 4 is about the Collectif d'Art Sociologique's (CAS) Social Realism. Rejecting traditional painting and sculpture, CAS shifted the emphasis onto the audience and made the reality of social relations appear concretely where they had otherwise been obscured by dominant ideology, making space for the constant renewal that defines democratic participation. This book will be of interest to scholars in art history, criticism and theory, and French cultural history and to readers interested in the global sixties"--